Osteopathic manipulative treatment in chronic coccydynia: A case series. Issue 2 (April 2018) - Origo, D.; Tarantino, A.G.; Nonis, A.; Vismara, L.
Abstract: Background: Coccydynia is a disorder associated with pain/discomfort at the base of the spine. The role of osteopathic manipulative treatment (OMT) in chronic coccydynia as well as for low back pain (LBP) and radicular pain (RP) associated with coccydynia, has not previously been investigated. This study seeks to analyse the effects of OMT on chronic coccydynia compared to physical therapy and pharmacological treatment (PTPT). The secondary objective is to analyse the effect of OMT on LBP and RP associated with coccydynia. Methods: Clinical records of 50 patients were examined. These patients (aged 39.94 ± 15.34 years, BMI 21.22 ± 3.15) who complained of chronic coccydynia were assessed 3 times: before any treatment (t0), after PTPT (t1) and after OMT (t2). Patients were treated with PTPT during the first 3 months and then referred by physicians to osteopaths to receive 3 sessions of OMT over a period of 5 weeks. The outcome measurements were made by a visual analogue scale (VAS 0–10 cm) and the Oswestry Low Back Pain Disability Questionnaire. Results: Before starting OMT treatment, patients showed a stable condition of coccydynia (mean VAS values from 7.1 to 6.5 p = 0.065) and a slight but significant reduction in disability (mean OD values from 17.7 to 14.5 p = 0.017) after PTPT. After the 3 sessions of OMT, all subjects gained a successful reduction in pain (mean VAS values from 6.5 to 1.2, p ≤ 0.001) and demonstrated a higher significant reduction in disability (mean Oswestry scale values from 14.5 to 2.5, p < 0.001). Conclusions: This case series shows that OMT elicits a positive benefit for pain relief and reduction in disability in patients complaining of coccydynia (with or without LBP and RP associated with coccydynia). Therefore, OMT could be considered as a valid therapeutic approach for treating chronic coccydynia. Nevertheless, further research is required to test the hypothesis and to better determine the benefits of OMT.